Modelling and analysis of barriers affecting the implementation of lean green agile manufacturing system (LGAMS). Issue 2 (4th March 2019) - Sindhwani, Rahul; Mittal, Varinder Kumar; Singh, Punj Lata; Aggarwal, Ankur; Gautam, Nishant
Abstract : Purpose: Many types of research have already investigated the lean, green or agile manufacturing systems in a discrete manner or as combinations of two of them. In today's competitive scenario, if industry wants to perpetuate its name in the market, then it has to supervene proper thinking and smart approach. Therefore, the combination of lean, green and agile manufacturing systems can provide better and beneficial results. The purpose of this paper is to discern the barriers to the combined lean green agile manufacturing system (LGAMS), understand their interdependence and develop a framework to enhance LGAMS by using total interpretive structural modeling (TISM) and MICMAC (Matriced' Impacts Croise's Multiplication Appliquée a UN Classement) Analysis. Design/methodology/approach: This paper uses TISM methodology and MICMAC analysis to deduce the interrelationships between the barriers and rank them accordingly. A total of 13 barriers have been identified through extensive literature review and discussion with experts. Findings: An integrated LGAMS has been presented that balances the lean, green and agile paradigms and can help supply chains become more efficient, streamlined and sustainable. Barriers are identified while referring to all three strategies to showcase the clear relevance. TISM models the barriers in different levels showcasing direct and important transitive relations. Further, MICMAC analysis distributes the barriers in four clusters in accordance with their driving and dependence power. Research limitations/implications: The inferences have been drawn from a model developed on the basis of inputs from a small fraction of the industry and academia and may show variations when considering the whole industry. Practical implications: The outcome of this research can contribute to bringing the change to the manufacturing systems used in most developing nations. Also, top managers considering adoption of LGAMS can be cautious of the most influential barriers. Originality/value: A TISM-based model of the barriers to an integrated LGAMS has been proposed with evaluation of the influence of the barriers.